POTRET KOMUNITAS REMAJA PENGGEMAR FOTOGRAFI (Studi pada Kelompok Belajar Fotografi Lampung KBFL) - Waluyo, Yolanda; Damayantie, Anita (SOCIOLOGIE, 2013)
Indonesia has been facing prolonged economic crisis that makes Indonesia is difficult to escape from poverty. The raise of social community in photography shows more increasing awareness of people to mitigate poverty. Photography is a natural way to obtain pictures of social life and to attract people attention to raise their empathies and sympathies upon objects taken in photography. A photography community in Bandar Lampung is Lampung Photography Learning Grup or KBFL. The problem statements in this research are what the backgrounds of teenaggers as members of KBFL are, how do the KBFL activty, and what are effects becoming KBFL community.This was a qualitative research with deep interview method. The results concluded that the background of teenagers to join the KBFL was photography hobby that was becoming a trend, life style, andÂ  to get wider relationships. KBFL conducted social activity in learning and deepening photography. Empathies to other people were increasing after joining KBFL, members had more self confidence by making more friends and realitionship.Keywords: Communities, adolescents, enthusiasts, photography